BENDI DALAM KARYA SENI GRAFIS - ANDRI AULIA RAHMAD, Irwan, Yofita Sandra (Serupa The Journal of Art Education, 2013)
The purposes of this final works of art are: 1) to defined bendi as a traditional transportation which is environment friendly art graphic creation, 2) to reveal the uniqueness of bendi that had been forgotten through graphic art creation. In creation process of graphic art, writer methodologically did some stage of exploration (seeking ideas) and implementation stages. Technique was using this final works of art is serigraphy. Along with technology progression, transportation tools are also had been developed. Although bendi is defeated by motor-vehicles, but it is still be used until now.Key word : graphic art, bendi